Still Loitering - Rolls, Alistair,Gosetti, Valentina (Peter Lang Ltd. International Academic Publishers, 2019)
Loiterature, perhaps Ross Chambers's most famous book, prescribes slow and careful reading practices but also quick-witted analysis. This collection draws together tributes, essays and critical responses to his wide-ranging work from Romanticism to the present, all demonstrating, through practice, the generative value of «loitering».
Description based on publisher supplied metadata and other sources
Keywords: Literatur